Antioxidant activity of chia flour as a food supplement in a cellular model: Repercussions of processing and in vitro digestion - Lucini Mas, Agustín (2024)
Food processing and digestion can alter bioactive compound composition of food, affecting their potential biological activity. In this study, we evaluated the direct and protective antioxidant effects of polyphenols extracted from defatted chia flour (DCF) (salviaflaside, rosmarinic and fertaric acid as major compounds), sweet cookies supplemented with DCF (CFC) (same major compounds), and their digested fractions (rosmarinic acid, salviaflaside, fertaric and salvianolic E/B/L acid as major compounds) in HepG2 cells in basal and in oxidative stress conditions. DCF showed protective antioxidant effects by decreasing reactive oxygen species (ROS) and protein oxidation products (POP) while increasing reduced glutathione (GSH). Additionally, CFC revealed similar protective effects and even showed enhanced modulation of the antioxidant system due to the activation of antioxidant enzymes. However, the digested fractions only decreased ROS, indicating continued antioxidant effects. This study underscores the importance of evaluating manufacturing and digestion effects to confirm a food’s antioxidant properties.